Analisis Penyerapan Tenaga Kerja Pada Sektor Pertanian di Indonesia - Theodora Melati; Idris Idris (Jurnal Kajian Ekonomi dan Pembangunan, 2023)
This study aims to analyze the factors that affect the absorption of labor in theagricultural sector in Indonesia. This research is classified as descriptive andassociative research. The data used is secondary data from 34 provinces inIndonesia in 2018-2021 obtained from BPS and other related institutions. Thisstudy uses panel data regression with a Fixed Effect Model approach which isprocessed using Eviews 9 software. The results show that the GRDP of theagricultural sector has a positive and significant effect on employment in theagricultural sector, the area of rice fields has a positive and insignificant effecton employment in the agricultural sector. In agriculture, the provincialminimum wage has a negative and insignificant effect on employment in theagricultural sector, the farmer's exchange rate has a positive and insignificanteffect on employment in the agricultural sector and the unemployment rate hasa positive and significant effect on employment in the agricultural sector.